THE DEVELOPMENT OF TOURISM VILLAGE THROUGH THE IMPLEMENTATION OF DIGITAL MARKETING - Gaffar, Vanessa; Yuliawati, Tia; Askolani, Askolani; Budiman, Arief (Pattimura University, 2023)
Introduction/Main objectives: This study aimed to analyze the implementation of digital marketing in the development of tourism village at Subang District area. Research Methods: This study is a qualitative study using case method, comparing the situation before and after the Covid-19 pandemic. The informant of this study consists of the head of regulator, namely the head of the village and the owner of micro, small, and medium enterprises. Finding/Results: Results show that Covid-19 pandemic affects the tourism potential in the area. This is proven by the low rate of attendance of visitors/tourists to the tourism destination in Cavaliering, Subang District. Therefore, to boost the rise of the visitor and to be able to cope with the environmental turbulence and uncertainty of the external environment, the local government should implement digital marketing. Conclusion: Through social media marketing which is part of digital marketing, the Small and Medium-Sized Enterprises (SMEs) could become more creative and innovative, which would help them expand their reach nationally and internationally. The government should allocate fund and include this in the long term planning of the village itself